Reliability and Statistics in Transportation and Communication Selected Papers from the 18th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'18, 17-20 October 2018, Riga, Latvia - Kabashkin, Igor.; Yatskiv (Jackiva), Irina; Prentkovskis, Olegas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reports on cutting-edge theories and methods for analyzing complex systems, such as transportation and communication networks and discusses multi-disciplinary approaches to dependability problems encountered when dealing with complex systems in practice. The book presents the most noteworthy methods and results discussed at the International Conference on Reliability and Statistics in Transportation and Communication (RelStat), which took place in Riga, Latvia on October 17 - 20, 2018. It spans a broad spectrum of topics, from mathematical models and design methodologies, to software engineering, data security and financial issues, as well as practical problems in technical systems, such as transportation and telecommunications, and in engineering education.
Keywords: Dynamics; Nonlinear theories; Transportation engineering; Traffic engineering; Telecommunication; Statistics .; Applied Dynamical Systems; Transportation Technology and Traffic Engineering; Communications Engineering, Networks; Applied Statistics